Comparison of three methods for determination of glucose - Dohnal, Luděk; Kalousová, Marta; Zima, Tomáš (Prague Medical Report, 2010)
Study refers comparison of three methods for glucose determination – precision (repeatability, reproducibility), traceability to SRM 965a NIST, comparability in blood-pools and in patients' samples: Electrochemical determination on Super GL (DiaSys, Germany) in hemolyzate – GL method, spectrophotometric determination using hexokinase (Glucose System Reagent 800, Olympus) – HKL method – and using glucose dehydrogenase (Glucose Gluc-DH, EcolineS+, DiaSys, Germany) – GDL method – in hemolyzate. For showing differences between the concentration of glucose in hemolyzed blood and corresponding plasma, spectrophotometric determination using hexokinase in plasma was used (Glucose System Reagent 800, Olympus) – HKP method. Coefficients of variation characterizing precision under repeatability and reproducibility conditions are not higher than 3.0% for the GL method, 6.3% for the GDL method and 15.8% for the HKL method with low sensitivity. For glucose concentration less than 8 mmol/l, HKL tends to give lower results than GDL, and GL tends to give higher results than GDL. For glucose concentration about 2 mmol/l, the results of glucose in plasma – HKP method – tend to be significantly lower (by more than ten percent) than in corresponding total (hemolyzed) blood. HKL method can be reasonably used in a high number of parallel determinations. For glucose 8 mmol/l and lower, comparability of results given by HKL, GDL and GL methods gradually worsens, while for glucose between 8 and 34 mmol/l results of the three mentioned methods are well comparable.
Keywords: krevní plazma; Humans; referenční standardy; Spectrophotometry; financování organizované; klinické laboratorní techniky; Financing, Organized; lidé; Blood Glucose; odběr vzorku krve; reprodukovatelnost výsledků; Reference Standards; Reproducibility of Results; Electrochemical Techniques; Plasma; krevní glukóza; Clinical Laboratory Techniques; spektrofotometrie; Statistics as Topic; statistika jako téma; elektrochemické techniky; kalibrace; Calibration; Blood Specimen Collection